Clinical assessment and follow up of post-operative outcomes in endonasal dacryocystorhinostomy: our experience - Ingale, Mayur H.; Shinde, Vinod V.; Kumar, Ashutosh S.; Singh, Harsh R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Endonasal dacryocystorhinostomy (DCR) was the gold standard for the treatment of nasolacrimal duct obstruction. The objective of the study was to assess the postoperative outcomes of endoscopic DCR. Methods: This prospective study was conducted in Department of Otorhinolaryngology, Dr. D. Y. Patil Medical College and Hospital Pimpri, Pune from July 2011 to September 2013. A total of 50 patients with complaints of continuous lacrimation were included in the study. All the patients underwent endoscopic DCR and they were observed for postoperative complications and outcome. Results: Most of the patients were in 31-40 years age group with the mean age of 33.18 years. Female dominance was observed in the study (M:F- 1:4). Postoperative complications such as epistaxis were observed in 2 cases (4.0%), nasal synechiae in 3 cases (6.0%) and postoperative crusting in 15 cases (30.0%). In 45 (90%) patients the outcome was successful at the end of 6 months and in case of 5 (10.0%) patients it was unsuccessful. Conclusions: The findings of the study concluded that endoscopic DCR was a simple, safe and invasive procedure as it has direct approach to the sac, produces excellent results without any external scar.